Analisis Resepsi pada Sentimen Publik Hiperrealitas Konsep Narsistik Edi Darmawan Salihin dalam Film Dokumenter 'Ice Cold' - Clarisa, Regina; Duva Dama, Muhammad Satrian (JURNAL LENSA MUTIARA KOMUNIKASI, 2024)
This research analyses the concepts of hyperreality and narcissism in the documentary film "Ice Cold: Murder, Coffee, and Jessica Wongso," directed by Rob Sixsmith, using Stuart Hall reception analysis. The analysis results show that this work strongly reflects hyperreality through the use of modern technology and audio-visual manipulation, which blurring the boundaries between reality and representation. Edi Darmawan Salihin, becomes a symbol of narcissism in this movie, with a focus on himself and his image as key elements in his identity construction. Stuart Hall's reception analysis also reveals that the signs in this film are not simply representations but also imply deep meaning, playing an important role in shaping the audience's understanding of the narrative and characters. This research contributes to understanding the concepts of hyperreality and narcissism in documentary works and opens up space for further studies in reception analysis. The conclusions of this research provide in-depth insight into aspects of reception in documentary works and provide a basis for further reflection regarding the use of Stuart Hall's reception analysis in understanding contemporary audio-visual art.